Prevalence and correction of near vision impairment at Kaski, Nepal - Sapkota, YD; Dulal, S; Pokharel, GP; Pant, B; Ellwein, LB (Nepalese Journal of Ophthalmology, 2012)
Introduction: Presbyopia is an important cause of avoidable visual disability. Objective: To estimate the prevalence of near vision impairment and spectacle coverage among middle and older-aged adults in rural Nepal. Materials and methods: The surveys was carried out among the people of age 35 and over in randomly-selected cluster samples in rural settings of Kaski district of western Nepal, Near visual acuity, with and without presenting near correction, was measured at 40 cm using a LogMAR near vision tumbling E chart under ambient indoor lighting. Subjects with uncorrected binocular distance vision of 20/40 or worse were refracted and those with near vision of 20/40 or worse tested with plus sphere to obtain the best-corrected binocular near visual acuity. Results: A total of 2,360 persons aged 35 years and over were enumerated and 2,156 (91.3 %) were examined. The age- and gender-standardized prevalence of uncorrected near visual impairment (vision of 20/40 or worse) in study population was found to be 66.1 %. Near vision could not be corrected (>20/40) even after distance and near vision correction in 6.4 % . Using the multiple logistic regression models, uncorrected visual impairment was associated with an older age (odds ratio [OR] = 1.13, P < 0.001) and a lower educational level (OR = 1.11, P = 0.01) was less associated with female gender (OR = 0.72, P = 0.038). Over 90 % of people with near visual impairment did not have spectacles. Conclusion: The prevalence of presbyopia appears to be higher with an earlier onset and over 90 % of people in need of near correction do not have spectacles in this setting. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5845 NEPJOPH 2012; 4(1): 17-22